A case study of potential human health impacts from petroleum coke transfer facilities. (1st November 2016) - Dourson, Michael L.; Chinkin, Lyle R.; MacIntosh, David L.; Finn, Jennifer A.; Brown, Kathleen W.; Reid, Stephen B.; Martinez, Jeanelle M.
ABSTRACT: Petroleum coke or "petcoke" is a solid material created during petroleum refinement and is distributed via transfer facilities that may be located in densely populated areas. The health impacts from petcoke exposure to residents living in proximity to such facilities were evaluated for a petcoke transfer facilities located in Chicago, Illinois. Site-specific, margin of safety (MOS) and margin of exposure (MOE) analyses were conducted using estimated airborne and dermal exposures. The exposure assessment was based on a combined measurement and modeling program that included multiyear on-site air monitoring, air dispersion modeling, and analyses of soil and surfaces in residential areas adjacent to two petcoke transfer facilities located in industrial areas. Airborne particulate matter less than 10 microns (PM10 ) were used as a marker for petcoke. Based on daily fence line monitoring, the average daily PM10 concentration at the KCBX Terminals measured on-site was 32 μg/m 3, with 89% of 24-hr average PM10 concentrations below 50 μg/m 3 and 99% below 100 μg/m 3 . A dispersion model estimated that the emission sources at the KCBX Terminals produced peak PM10 levels attributed to the petcoke facility at the most highly impacted residence of 11 μg/m 3 on an annual average basis and 54 μg/m 3 on 24-hr average basis. Chemical indicators of petcoke in soil and surface samples collected from residential neighborhoods adjacent to the facilities were equivalent to levels in corresponding samples collected at reference locations elsewhere in Chicago, a finding that is consistent with limited potential for off-site exposure indicated by the fence line monitoring and air dispersion modeling. The MOE based upon dispersion model estimates ranged from 800 to 900 for potential inhalation, the primary route of concern for particulate matter. This indicates a low likelihood of adverse health effects in the surrounding community. Implications : Handling of petroleum coke at bulk material transfer facilities has been identified as a concern for the public health of surrounding populations. The current assessment, based on measurements and modeling of two facilities located in a densely populated urban area, indicates that petcoke transport and accumulation in off-site locations is minimal. In addition, estimated human exposures, if any, are well below levels that could be anticipated to produce adverse health effects in the general population.